Evaluasi Efek Terapeutik Terhadap ISPA Serta Status Gizi Anak Balita - M. Sabir; Sarifuddin Sarifuddin (Biology Department, Mathematics and natural science, Tadulako University, 2010)
The study is devoted to investigating the therapeutic effect on severity of acute respiratory infection (ARI) and nutritional status of underfive years old. It is analytic design of evaluative by visiting the house of sample at the fourth until the ninth days after giving therapeutic. The number of sample was 50 under five years old, selected by accidental sampling. The data were analyzed with wilcoxon sign runk test and paired t-test. The study indicated that first diagnoses of acute respiratory infection severity, it was found that average of duration of ARI was 3 days (17%), severe ARI is 84% and mild ARI 16%. Based on nutritional status (weight/age = W/A), severe malnutrition (8%), undernutrion (16%), and well nutrition (76%). The fourth days of therapy was found that duration of ARI was six days (66%) and severe ARI (52%), mild ARI (32%) and healing (16%). Meanwhile, nutritional status was severe malnutrition (6%), undernutrition (20%) and well nutrition (20%). The nine days of therapy, duration of ARI was six days (56%), severe ARI was 20%, mild ARI was 34% and healing was 46%. Severe malnutrition was 6%, undernutrition was 18%, and well nutrition was 76%. Paired T-test and Wilcoxon test, shown that there was therapeutic effect on duration and severity of ARI (P = 0,000) and (P = 0,004), and no effect of nutritional status based on paired t-test (P = 0,748). The conclusion is therapeutic can reduce of duration and severe of ARI, meanwhile nutritional status dose not have effect. Key words: Therapeutic effect, severity of ARI, nutritional status, underfive years old.